The Effect of the Employee Income Supplement (Tpp) and Work Effective-ness on Employee Performance within the Regional Secretariat of Oku Re-gency - Selpi Yandri; Yunita Sari; Yetty Oktarina (Institute for Law and Economics Studies, 2026)
This study aims to analyze the influence of Employee Income Allowance (TPP) and Work Effectiveness on Employee Performance among Civil Servants (ASN) within the OKU Regency Regional Secretariat. The research method used is quantitative descriptive with a statistical approach to describe the relationship between variables. The research population consisted of 141 employees, with a sample of 59 respondents determined using probability sampling through simple random sampling based on the Slovin formula with a 10% margin of error. Data collection was conducted via a questionnaire using a 1–5 Likert scale, supported by observation and documentation. Validity and reliability tests indicated that all research instruments were suitable for use. Data analysis was performed using multiple linear regression with the aid of SPSS version 26 software, following classical assumption tests that included tests for normality, multicollinearity, and heteroscedasticity. The results of the study indicate that, individually, TPP and Work Effectiveness have a significant effect on Employee Performance. Simultaneously, these two independent variables also have a significant influence on the dependent variable. The coefficient of determination indicates that TPP and Work Effectiveness can explain most of the variation in Employee Performance. Thus, improving welfare through TPP and optimizing work effectiveness can be important factors in enhancing civil servant performance